Pemberdayaan Perempuan Berbasis Kelompok Wanita Tani Mandiri Asri Gilingan Surakarta dalam Penguatan Ekonomi Sirkular dan Pengelolaan Sampah Berkelanjutan - Zandra Dwanita Widodo; Sri Wijiastuti; Darsono Darsono; Dhea Sashinta Ashari; FA. Luky Primantari; Istinganah Eni Maryanti; Fandi Achmad Ghani; Maulana Wati; Denny Zaki Alfalaq; Fajar Budi Setiawan (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2026)
This community service activity was motivated by the suboptimal human resource capacity of the Asri Gilingan Surakarta Mandiri Women Farmers Group in utilizing appropriate technology to support a circular economy and household waste processing. The main problems of partners include limited knowledge in utilizing yards, low skills in processing organic waste into compost or ready-to-sell planting media, and the lack of a sustainable group activity management system. The purpose of this activity is to increase the knowledge, skills, and independence of KWT Mandiri Asri members in applying appropriate technology based on local potential to support a circular economy and reduce household waste. The implementation method is carried out through a participatory-educational approach that includes identifying partner needs, appropriate technology training, direct practice of processing ready-to-sell organic waste, utilizing yards for food crops, group discussions, and mentoring in implementing training results. The results of the activity through pre-tests and post-tests showed an increase in understanding of appropriate technology to process waste into ready-to-sell products from 36% to 54%, the ability to sort waste from 32% to 64%, and the ability to record simple things from 24% to 56%. Furthermore, this activity encourages increased member participation in environmental management and strengthens group institutions. In conclusion, strengthening human resource capacity through appropriate technology can positively contribute to improving the skills of KWT Mandiri Asri members, managing household waste, and strengthening the community-based circular economy. Sustainability of this activity requires continued mentoring so that the practices learned can be consistently implemented and developed into a model for empowering productive, independent, and environmentally friendly urban women.